Meh Sini Enterprise: cyber café and 3D printing / Wan Muhamad Syakirin Mhd Sanusi... [et al.] - Mhd Sanusi, Wan Muhamad Syakirin; Surani, Muhammad Danish; Zulkiple, Muhammad Zaim; Mutsapha Kamal, Syazwan Hakim; Ishak, Izzat (2017)
Meh Sini 3D Printing is a company which focuses on 3D printed production in Malaysia. We also include small cyber café inside our shop, just for simple medium to make some research before print the product or surfing the internet.